Onset of Type I Diabetes Followed by Scleroderma Syndrome in a Child After the COVID-19: A Case Report - Ievgeniia Burlaka PhD; Inga Mityuryayeva PhD; Olena Sevastiian MD; Ivanna Kachula MD (SAGE Publishing, 2024)
Morphea, is a chronic inflammatory disease of the dermis and subcutaneous tissue. Research has indicated a connection between morphea and Type I Diabetes (T1D). COVID-19 can cause autoimmune diseases like scleroderma, T1D, systemic lupus erythematosus, and others. A 12-year-old girl with type 1 diabetes who was on insulin therapy was brought into the clinic for a metabolic evaluation. The patient had induration, skin hardness, and cutaneous erythema upon inspection. The onset of T1D was following a mild COVID-19 infection. Signs of morphea merged 3 months after the onset of T1D. Known as "long-term COVID," this sickness phase that follows the acute stage of COVID-19 is most likely the result of autoimmune activation. As this patient under evaluation reveals, COVID-19 has been demonstrated in the literature to cause the production of autoantibodies and to either cause or worsen autoimmune disorders in people who have a genetic susceptibility.